Revision Notes for MRCP 2 PACES - Rahman Shibley, Sharma Avinash; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2010)
The Royal College of Physicians believe that have developed an examination, which they intend to be fair and to be an appropriate test of postgraduate knowledge in Doctors preparing for higher specialist training and since 2001 the examination has been running very successfully. The academic aims of the MRCP (UK) examination are stated clearly: (i) To test a wide range of up-to-date medical knowledge so that physicians in training are encouraged to develop their full clinical and professional potential, (ii) To maintain and improve the practice of clinical medicine, and (iii) To provide a sound basis for continuing medical education. Much of this book has been derived from authors; own experiences regarding the examination, and where possible sample instructions have been given for individual cases in the real examination. However, the content of the book closely follows the syllabus as published in the MRCP Clinical Guidelines. The authors to their knowledge have been aware of all of these cases having appeared in the Membership clinical examination at least once. Management issues/guidance/protocols are all subject to change with time, and therefore the reader is advised to supplement his/her reading with other sources, for example, from the Royal College of Physicians or the National Institute of Clinical Excellence. Whilst the delivery of the examination is possibly subject to change with modernisation of the medical curriculum, the content of the higher specialist training is unlikely to change in the imminent future. The marksheets are available in the Clinical Guidelines and on the website. Much of this book has been derived from a synthesis of teaching and examining for the examination nationally in the UK, although the standards in international centres are exactly the same as in the UK.
Keywords: MCQs and Self-assessment,Medicine; Electronic books